Pengembangan Bio-Booklet Materi Sistem Imun untuk Mengoptimalkan Hasil Belajar Siswa SMA - Futri Dalle; Muhammad Mifta Fausan; Ramlah; Indah Panca Pujiastuti (Jurnal Biologi dan Pembelajarannya (JB&P), 2026)
Biology learning on the Immune System topic requires instructional media capable of presenting concepts in a concise, systematic, and easily comprehensible manner. This research focused on creating a Bio-Booklet on the Immune System for Grade XI senior high school students, ensuring it met standards of validity, practicality, and effectiveness. The study utilized a research and development methodology based on the ADDIE model, which includes stages of analysis, design, development, implementation, and evaluation. Validation of the Bio-Booklet was conducted by an expert in the subject matter, a media specialist, and a practitioner (biology teacher). The product trial involved Grade XI and Grade XII students as research subjects. The research tools included a validation form, a questionnaire for student feedback, and an assessment of learning achievements. The results showed that the Bio-Booklet achieved validity levels categorized as valid to highly valid, practicality levels categorized as highly practical, and was effective in improving students’ learning outcomes based on the Wilcoxon Signed Ranks Test. Therefore, the Bio-Booklet serves as a suitable educational tool for teaching the topic of the Immune System at the senior high school level.